Atlas of oceans an ecological survey of underwater life - Farndon, John (Yale University Press, 2011)
Although many books have explored the environmental problems being faced on land, Atlas of Oceans is the first book for a general audience that examines how creatures of the marine environment are if anything more vulnerable than their land-based counterparts.